The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1128/msystems.00743-19
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Crude Oil and Dispersant on the Larval Sponge Holobiont

Abstract: Larvae of the sponge R. odorabile survived exposure to high concentrations of petroleum hydrocarbons; however, their ability to settle and metamorphose was adversely affected at environmentally relevant concentrations, and these effects were paralleled by marked changes in sponge gene expression and preceded by disruption of the symbiotic microbiome. Given the ecological importance of sponges, uncontrolled hydrocarbon releases from shipping accidents or production could affect sponge recruitment, which would h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 114 publications
(137 reference statements)
0
10
0
Order By: Relevance
“…Heat shock genes code for highly conserved proteins, which act as molecular chaperones (Liu et al, 2015a). Specifically, Hsp70 and Hsp90 play a key role in the metabolic detoxification of toxic stressors including PAHs, pesticides or heavy metals (Regoli and Giuliani, 2014) and were also found up-regulated in sponge R. odorabile larvae exposed to WAF and CEWAF (Luter et al, 2019). Hsp70 help to clear aggregated proteins and suppress the ability of cells to undergo apoptosis (Liu et al, 2015a).…”
Section: Gene Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heat shock genes code for highly conserved proteins, which act as molecular chaperones (Liu et al, 2015a). Specifically, Hsp70 and Hsp90 play a key role in the metabolic detoxification of toxic stressors including PAHs, pesticides or heavy metals (Regoli and Giuliani, 2014) and were also found up-regulated in sponge R. odorabile larvae exposed to WAF and CEWAF (Luter et al, 2019). Hsp70 help to clear aggregated proteins and suppress the ability of cells to undergo apoptosis (Liu et al, 2015a).…”
Section: Gene Expressionmentioning
confidence: 99%
“…However, many studies using WAFs and CEWAFs have shown that dispersants can themselves be toxic or increase the concentration of hydrocarbon in seawater and amplify hydrocarbon bioavailability for marine organisms (Ramachandran et al, 2004;Rodd et al, 2014). The use of chemical dispersants therefore is controversial (Kleindienst et al, 2015) and further work is needed to understand the impact of dispersant on non-model organisms with important roles in ecosystem function, such as sponges (Luter et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A clear picture of MMT, or the higher impact of one transmission mode over the other, will only emerge if representative samples for each one of these modes are recovered and correspondingly studied during the survey. Assessment of the role of microbial transmission on adaptative responses of the sponge holobiont to a myriad of environmental factors. To our account, there are only two reports where this issue was initially perceived (Webster et al ., 2010; Luter et al ., 2019). Adequate experimental setups under controlled conditions will make a considerable difference when addressing this aspect, which deserves special attention given the dramatic effects of climate change and the deleterious effects of direct anthropogenic action (e.g., oils spills, industrial discharge, erosive exploitation of coral reefs for tourism/commercial activities) on natural habitats of these invertebrates.…”
Section: Discussionmentioning
confidence: 99%
“…The same research group investigated the effects of the exposure to hydrocarbon pollutants (crude oil fractions) on the microbiome associated with the same host model ( R. odorabile ). The microbiome detected in larvae turned out to be significantly affected after exposure to different formulations of crude oil, with the loss of a key ammonia‐oxidizing thaumarchaeal symbiont (Luter et al ., 2019). Interestingly, several OTUs encountered after the hydrocarbon treatments shared high similarity with sponge‐ or coral‐associated clusters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation